Do low-income parents who receive unemployment insurance pay more child support?. (April 2020) - Hodges, Leslie
Highlights: UI benefits are positively associated with child support payments and compliance. Wage withholding from UI may be an effective child support enforcement tool. Referrals to UI programs may be beneficial for unemployed noncustodial parents. Abstract: This paper investigates the relationship between receipt of unemployment insurance (UI) benefits and formal child support payments and compliance among low-income parents experiencing employment difficulties. In theory, receipt of UI benefits may help noncustodial parents experiencing employment difficulties continue to meet their child support obligations. Under federal law, child support agencies can collect child support from unemployment insurance benefits received by noncustodial parents on IV-D cases. In practice, take-up of UI is quite low, particularly among low-income workers. In order to learn more about the relationship between unemployment insurance and child support payments, this paper uses survey and administrative data from a federally funded eight-state intervention for noncustodial parents. Findings from individual-level fixed effect models indicate that UI receipt is associated with increases in child support payments and compliance. These findings suggest that UI can be an important source of economic support for children living apart from the parent receiving benefits. These findings also highlight the potential for service connections between child support and UI agencies to support noncustodial parents in meeting their child support obligations and the continued importance of expanding economically disadvantaged workers' access to the UI program.